Application of Mn-Fe Layered Double Hydroxide as an Adsorbent for the Removal of Arsenic from Synthetic Acid Mine Drainage - Irawan, Chairul -; Sari, Ayu Ratma; Yulianingtias, Aproditha; Melinda, Rizani Aulia; Mirwan, Agus (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
The Mn-Fe layered double hydroxide using chloride in the interlayer anion was successfully synthesizedusing chemical co-precipitation methods. The Mn-Fe LDH was then applied as adsorbent for arsenic removal from synthetic acid mine drainage. The adsorbent characterizations of SEM and XRD analysis showed that the Mn-Fe LDH had many different functional groups and a high specific surface area for the adsorption processes. The morphological structure of Mn-Fe LDH by the SEM-EDS analysis method shows a round shape structure with a particle size of about 1 m, and the XRF analysis method shows that the Mn and Fe elements dominate more than other components. Batch adsorption experimental conducted using the Mn-Fe LDH with the interlayer anion of chloride as an adsorbent to study the effect of contact time, equilibrium pH, and temperature on the arsenic removal. The Mn-Fe LDH showed high adsorption uptake capacity and selectivity for the arsenic in the synthetic acid mine drainage. The adsorption and ion exchange between interlayer chloride anions in Mn-Fe LDH and As (V) solution was the main adsorption mechanism. Therefore, the Mn-Fe LDH can be used as an adsorbent in water and wastewater treatment. In contrast, this research has the potential to be processed and developed into advanced materials.